BONE MINERAL DENSITY AND VITAMIN D RECEPTOR GENETIC VARIANTS IN EGYPTIAN CHILDREN WITH BETA THALASSEMIA ON VITAMIN D SUPPLEMENTATION - Hadeer A Abbassy; Reham Abdel Haleem Abo Elwafa; Omneya Magdy Omar (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Low bone mineral density (BMD) is a characteristic feature of Beta thalassemia major (βTM) patients. Vitamin D is important for bone mineralization. Vitamin D receptors (VDR) genetic variants may be related to vitamin D status and BMD.